Effectiveness and safety of intravenous ferric carboxy maltose in anaemic women attending gynecological unit - R., Bharathi K.; Bhat, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Anaemia is a significant problem worldwide, particularly in women. Several intravenous iron preparations are available for the treatment of anaemia. Some of them cause life-threatening anaphylactic reactions while others require multiple small infusions to prevent iron reactions. Ferric carboxy maltose (FCM), a non-dextran intravenous iron, is safe and effective option that can be administered as single high dose without serious adverse effects. Methods: A prospective study was undertaken in the department of obstetrics and gynecology, Adichunchungiri institute of medical sciences, B G Nagara, from August 2020 to November 2021 in which 50 cases with iron deficiency anaemia were enrolled. IV FCM 1g was given. Change in the laboratory parameters such as haemoglobin (Hb), mean corpuscular value, serum ferritin levels over a 4 weeks period were observed. Results: A significant increase in mean Hb from 8.14 to 11.71 g was observed in patients treated with FCM after 4 weeks of therapy. Majority belonged to age group of 21-30 years and moderate type of anaemia was most common. No serious drug reaction was reported. Conclusions: IV FCM is safe and effective option for improving Hb in iron deficiency anaemia, in terms of restoring iron stores in short duration of time as well as patient compliance.